Protective Effects of Hydro-alcoholic Extract of Apium Graveolens on Carbon Tetrachloride Induced Hepatotoxicity in Sprague-Dawley male Rats - Zahra Talebanpour bayat; Heydar Aqababa; Manzar Banoo Shojaiefard (Fasa University of Medical Sciences, 2015)
Background & Objective: Apium graveolens has antioxidant property because of its flavonoid compounds. In the present study, we investigated the hepatoprotective effects of hydroalcoholic extract of Apium graveolens in Sprague Dawley male rats treated with carbon tetrachloride (CCl4). Materials & Methods: In this study, 48 rats (weighted 180-200 gram) were divided into six groups each having eight rats. The six groups were control, sham, CCl4, and three experimental groups. The experimental groups (4-6) received 1ml/kg CCl4 twice a week and olive oil with the ratio of 1:1 by intraperitoneal injection for 40 days. In addition, they received 2 cc hydroalcoholic extract of Apium graveolens by daily gavage with the concentrations of 200, 400, and 600 mg/kg/cc, respectively. The sham group received only olive oil with the mentioned ratio and the other group received CCl4 and olive oil. At the end, Alkaline Phosphatase (ALP), Aspartate amino Transferase (AST), Alanine amino Transferase (ALT), and the serum concentrations of albumin, total and direct bilirubin were measured and analyzed by using statistical ANOVA Test.   Results: Injection of CCl4 increased the serum levels of liver enzymes and total and direct bilirubin but it decreased the concentration of serum albumin. On the other hand, hydroalcoholic extract of Apium graveolens decreased the liver enzymes and increased albumin level (p<0.001).   Conclusion: The results of this study reveals that the consumption of hydro-alcoholic extract of Apium graveolens maintain the integrity of the liver and protects it against damage.